Reassessing the dosing of cefoxitin prophylaxis during major abdominal surgery: insights from microdialysis and population pharmacokinetic modelling. (9th April 2019) - Boisson, Matthieu; Torres, Bruna Gaelzer Silva; Yani, Sabrina; Couet, William; Mimoz, Olivier; Dahyot-Fizelier, Claire; Marchand, Sandrine; Grégoire, Nicolas
Abstract: Objectives: Cefoxitin is frequently used for surgical antibiotic prophylaxis (SAP). Using microdialysis, we evaluated whether the currently recommended dosing regimen is appropriate to maintain cefoxitin subcutaneous tissue concentrations above the MIC for pathogens involved in abdominal surgical site infection. Methods: Data from eight patients undergoing major abdominal surgery were analysed using population pharmacokinetic modelling, and Monte Carlo simulations were conducted to determine the PTA for aerobic and anaerobic pathogens. ClinicalTrials.gov: NCT02703857. Results: Only 2.3% and 47.4% of the simulated patients maintained cefoxitin subcutaneous concentrations above the MIC breakpoint for anaerobic (MIC = 16 mg/L) and aerobic (MIC = 8 mg/L) pathogens, respectively. New simulations with administration of a loading dose followed by a constant infusion of cefoxitin were conducted and demonstrate that, notwithstanding using the same total dose per unit of time, continuous infusion of cefoxitin can cover aerobes in 96.6% of the simulated patients, but remains insufficient for anaerobic bacteria. Conclusions: The recommended dosing regimen of cefoxitin is insufficient for covering the usual bacteria during abdominal surgery. Administration of a loading dose followed by a constant infusion should be considered for aerobic bacteria and cefoxitin should be avoided as SAP for anaerobic bacteria.